2015
DOI: 10.1007/s40093-015-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of chemical changes through production of various composts/vermicompost such as farm manure and sugar industry wastes

Abstract: Purpose Owing to aridity in our agro-ecosystem, mineralization of organic substrate is quite rapid and thereafter volatilized due to lower matrix affinity. In these consequences, the study has been chalked out with the hypothesis to alter the best approaches for mineralization of available organic resources as soil supplement to reduce the economic burden on the farming community. Our laboratory study showed the sequential temporal variations in physic-chemical properties of available organic substrates such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…The amount of compost and/ or FYM that provided optimum agronomic and economic yields could further be reduced and hence their MRR increased by vermicomposting. Shah et al (2015) reported that farm manure inoculated with local species of earthworms produced best quality manure with enriched nutritional status including 3% N. This result was found almost two fold of the values obtained in the current study (1.76 and 1.64% N in 2013 and 2014, respectively) implying that the amount of organic fertilizers and their associated costs could further be reduced by enhancing their quality.…”
Section: Economic Analysissupporting
confidence: 72%
“…The amount of compost and/ or FYM that provided optimum agronomic and economic yields could further be reduced and hence their MRR increased by vermicomposting. Shah et al (2015) reported that farm manure inoculated with local species of earthworms produced best quality manure with enriched nutritional status including 3% N. This result was found almost two fold of the values obtained in the current study (1.76 and 1.64% N in 2013 and 2014, respectively) implying that the amount of organic fertilizers and their associated costs could further be reduced by enhancing their quality.…”
Section: Economic Analysissupporting
confidence: 72%
“…From the genotoxicity study, the results indicated that the vermitechnology reduced the genotoxicity potential of sugar beet mud. Shah et al [28] conducted vermicomposting of sugarcane baggase, pressmud, along with sugar mill effluent and farm manure. The final vermicompost of sugar mill wastes produced high quality manure with enriched nutrients (N, P, K, Ca, Na).…”
mentioning
confidence: 99%
“…The pH was almost same at 6.75 in aerobic-compost and 6.73 in vermi-compost. Reasonably higher nutrient contents in the compost types were probably due to better decomposition (Shah et al 2015), and enrichment with rock phosphate and urea.…”
Section: Chemical Analysis Of Compostmentioning
confidence: 94%